Bifacial Elements in Continental Northwestern Europe during the Last Glacial Cycle (MIS5d-3): The Relationship between Mousterian, Micoquian and ‘Mixed’ Assemblages. - Karen Reubens (Papers from the Institute of Archaeology, 2007)
Based on the different bifacial elements that occur in the last glacial cycle it is established that at least three technocomplexes can be distinguished in continental northwestern Europe: Mousterian of Acheulean Tradition (small, symmetric, cordiform and triangular handaxes), Micoquian or Keilmessergruppe (asymmetric bifacial elements, often with backing and noncovering retouched) and a leaf point industry. Moreover, the analyses show that some lithic assemblages in continental northwestern Europe do not fit into this current framework of Middle Palaeolithic industries. More specifically assemblages that contain a contemporary presence of Micoquian and Mousterian bifacial elements occur regularly, leaving a typological dilemma to assign them to one of these two technocomplexes. This leads to the question: do Micoquian and Mousterian industries represent behaviourally discrete entities and how do ‘mixed’ assemblages fit into this? After exploring the techno-typological characteristics of these ‘mixed’ assemblages, possible reasons for the variability in bifacial elements and the causes for the occurrence of mixed assemblages, including the relationship between the Micoquian and Mousterian, are presented. Interpreting this phenomenon is preliminary since the evidence is coarse-grained due to many old excavations and a lack of chronostratigraphic information. Most likely the mixed occurrences can be explained in relation to population migrations caused by climate change.